Bartending: Knowledge, Attitude, and Practices among Bar Employees in Selected Resorts in Boracay Island - Gaviola, Manuel A.; Maming, Jimmy Bernabe (Future Science / FSH-PH Publications, 2022)
This investigation aims determine the bartenders’ mindset, behaviors, and skills in mixing drinks on Boracay, a popular tourist attraction in the Philippines. The basic random sample approach was used to pick 98 bar personnel from various Boracay resorts as participants. During the data gathering, Domille (2013) Bartender's Test on Knowledge of Bartending as well as the TESDA Self-assessment Guide for the Certificate Program II were used, as well as probability, percentages, average, variance, t-test, one-way ANOVA, and Pearsons r. The interviewees were divided into groups as to their gender, age, socioeconomic status, education level, length of engagement, and monthly compensation. According to the findings, employees in Boracay Island are highly competent, have a positive mindset to bar work, and practice bartending extensively.